Sensitivity of Pulsatility index of Uterine Artery on Doppler Ultrasound in Diagnosis of Polycystic Ovarian Syndrome - Roshna Qamar, Muhammad Usman Farooq Baig, Rabia Ashraf, Maria Babar, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: This study was planned to explore the sensitivity of uterine artery PI and RI. Method: This descriptive Observational study was carried out in Department of Radiology, Combined Military Hospital, Lahore, within six months after the approval of synopsis. Calculated sample size was of 120 females. The collected data was entered and analyzed by using software SPSS version 25.0. Man and standard deviation was calculated for PI and RI. Frequency and percentage was calculated for sensitivity of Pulsatility Index of uterine artery on 3D Doppler for polycystic ovarian syndrome diagnosis. Results: The accurate diagnosis of PCOs among patients was 80.83%. The results revealed that mean pulstility index of right uterine artery was 2.83±0.99 and for Left uterine artery, it was 1.37±0.69 whereas the combine mean was 2.1±0.84. Similarly, mean value of Resistive Index for right uterine artery was .83±.75 and for Left uterine artery, it was .59±.21 whereas the combine mean was 0.71±0.48. Conclusion: The accuracy of polycystic ovarian syndrome diagnosis is quite high with pelvic color Doppler which supports the usage of color Doppler for the diagnosis of polycystic syndrome in females. Keywords: Polycystic Ovarian Syndrome, Pulsatility Index, Resistive Index